2019
DOI: 10.1021/acsami.9b10158
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution of Au@Pt Core–Shell Nanoparticles under Electrochemical Polarization

Abstract: Understanding the microstructural evolution of bimetallic Pt nanoparticles under electrochemical polarization is critical to developing durable fuel cell catalysts. In this work, we develop a colloidal synthetic method to generate core–shell Au@Pt nanoparticles of varying surface Pt coverages to understand how as-synthesized bimetallic microstructure influences nanoparticle structural evolution during formic acid oxidation. By comparing the electrochemical and structural properties of our Au@Pt core–shells wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…The X-ray photoelectron spectra for Au 2% /TiO 2 and Pt 2% /TiO 2 are presented in Figure S7. Au/TiO 2 exhibits a doublet at 4f 7/2 = 84.2 eV and 4f 5/2 = 87.9 eV, corresponding to the metallic Au nanoparticles (Au 0 ), while Pt/TiO 2 exhibits a doublet at 4f 7/2 = 70.8 eV and 4f 5/2 = 74.1 eV, corresponding to the metallic Pt nanoparticles (Pt 0 ) . Therefore, XPS analysis confirms that both types of nanoparticles are metallic, without a significant presence of oxides.…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…The X-ray photoelectron spectra for Au 2% /TiO 2 and Pt 2% /TiO 2 are presented in Figure S7. Au/TiO 2 exhibits a doublet at 4f 7/2 = 84.2 eV and 4f 5/2 = 87.9 eV, corresponding to the metallic Au nanoparticles (Au 0 ), while Pt/TiO 2 exhibits a doublet at 4f 7/2 = 70.8 eV and 4f 5/2 = 74.1 eV, corresponding to the metallic Pt nanoparticles (Pt 0 ) . Therefore, XPS analysis confirms that both types of nanoparticles are metallic, without a significant presence of oxides.…”
Section: Methodsmentioning
confidence: 67%
“…Au/TiO 2 exhibits a doublet at 4f 7/2 = 84.2 eV and 4f 5/2 = 87.9 eV, corresponding to the metallic Au nanoparticles (Au 0 ), while Pt/TiO 2 exhibits a doublet at 4f 7/2 = 70.8 eV and 4f 5/2 = 74.1 eV, corresponding to the metallic Pt nanoparticles (Pt 0 ). 16 Therefore, XPS analysis confirms that both types of nanoparticles are metallic, without a significant presence of oxides. Performing the photodeposition under inert atmosphere at pH ≈ 6 using a high concentration of methanol, i.e., 2.7 mol L −1 , would likely result in an almost complete conversion of the metal salts to their metallic state regardless of the loading amount.…”
Section: Methodsmentioning
confidence: 72%
“…The results showed that in presence of CO, Pt diffuses to the surface, allowing the formation of strong Pt-CO bonds [50]. In contrast, when Pt metal is encapsulated by Au (Pt@Au), the catalytic activity diminished due to the CO oxidation does not occur at the cluster surfaces that are initially pure Au [51].…”
Section: Resultsmentioning
confidence: 99%
“…[9][10][11][12] It is becoming increasingly clear, however, that these types of pretreatments can significantly alter the properties of the catalysts under study. For example, following pretreatment, structured bimetallic NPs can undergo atomic rearrangements, [13][14][15][16] the crystal structure, shape, and facets can change, [4,[17][18][19] and atoms can undergo selective dissolution. [7,8,13,16,[20][21][22] Even for polycrystalline gold surfaces, the rate of anodic Au dissolution during potential cycling is highly dependent on the surface structure of the electrode.…”
Section: Introductionmentioning
confidence: 99%